Individualism in a Stable Democracy as the Decisive Factor of the Progress of Behavioralism in the Development of American Political Science Post World War II - Bambang Wahyu Nugroho (Universitas Muhammadiyah Yogyakarta, 2012)
Since the end of World War II, the development of American political science showed the behavioral persuasion as the dominant one. Behavioralism had many factors and its rapid growth had a great impact on the development of political studies. Even in the recent times, no one deny that the American political science is the most influential school on the study of politics all over the world. In short, comparing to the other part of the world, the development of political science in America is revolutionary rather than evolutionary. Many scientists have written about the factors causing the rapid spring of behavioralism in American Political Science. However, this work is done to examine other significant factors. The question does not begin from “why American Political Science growing rapidly?” but “Why facts show us there was a slow motion growth of political science out of America?” I think that the answer is laid on individualism as a philosophy and/or ideology. Individualism is a belief in the primacy of the individual over any social group or collective body, so it will suggest that the individual is central to any political theory or social explanation. Individualism influenced political scientists to focus the unit of analysis on the individual behavior to explain collective phenomenon. We can see then, in other parts of the world, when stable liberal-democracy based on individualism occur, the social sciences can develop well. Maybe this is another unique characteristic of political science. The growth of political science depends on its political circumstances.